Tmprss3 is expressed in several cell types of the inner ear including type II but hardly in type I spiral ganglion neurons - Arora, Ramil; Pifková, Lucie; Deutschmann, André Ulrich; Reisinger, Ellen (Frontiers in Cellular Neuroscience, 2025)
Mutations in the transmembrane serine protease 3 gene (TMPRSS3) cause non-syndromic hearing impairment, with congenital (DFNB10) or late childhood onset (DFNB8). In some reports, these patients were found to have lower speech comprehension scores with cochlear implants (CIs) compared to CI users with other etiologies. Since CIs electrically stimulate spiral ganglion neurons (SGNs) to activate the auditory pathway, TMPRSS3 deficiency was presumed to cause a dysfunction or degeneration of these cells, of which type I SGNs form the predominant group. Here, we revisited the expression pattern of Tmprss3 in the developing and mature mouse inner ear on mRNA level with quantitative few-cell PCR and RNAscope, and on protein level with immunohistochemistry with an anti-TMPRSS3 antibody validated on knock-out tissue. In the organ of Corti, we demonstrate expression of Tmprss3 in inner and outer hair cells, particularly in the stereocilia, and in pillar cells. Furthermore, expression of this gene in root cells of the lateral wall close to the stria vascularis indicates a potential function in K+ recycling, and expression in the spiral limbus may be linked to the generation of the tectorial membrane. Within Rosenthal’s canal, in immature tissue, Tmprss3 was diffusely expressed in all SGNs, but in the mature ear, in type I SGNs we found only minor mRNA amounts with qPCR, RNAscope, and no specific immunolabeling. In contrast, in type II SGNs Tmprss3 expression is enhanced during maturation. We hypothesize that the background levels of Tmprss3 expression in type I SGNs are not directly responsible for the vitality of these neurons, and that indirect effects, like signaling cascades dependent on TMPRSS3 in other cell types, are crucial for type I SGN function and survival.